The Effect of Guided Reading Procedure and Students’ Motivation toward Students’ Narrative Reading Comprehension Achievement of the Tenth Grade Students of SMA Bina Warga 2 Palembang - Andriamella Elfarissyah (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT This study was meant to reveal the effect of guided reading procedure and students’ motivation toward students’ narrative reading comprehension achievement of the tenth grade students of SMA Bina Warga 2 Palembang, including to find whether or not (1) guided reading procedure affects the students’ narrative reading comprehension achievement and (2) there is any interaction effect of method used and motivation on the students’ reading comprehension achievement.The population of this study was the tenth grade students of SMA Bina Warga 2 Palembang in the academic year 2012-2013 consisting of 239 students. The sample was selected by using two-stage random sampling. From the sample, 48 students were taken as her research sample. 24 students represented in an experimental class and control class. The data were collected by using questionnaire and test. The quantitative research was used as the approach of this study. In carrying out this research, a factorial design was used.From the finding of the research, it can be concluded that: (1) there was a significant interaction effect of motivation on students’ narrative reading comprehension achievement taught using guided reading procedure and conventional strategy. It was found the p-output 0.043 was lower than 0.05. It means that (Ho) is rejected and (Ha) is accepted; and (2) there was no any interaction effect of method used and motivation on the students’ reading comprehension achievement. It was found that the p-output was 0.178 was higher than 0.05. It means that (Ho) is accepted and (Ha) is rejected. The Key Words: Guided Reading Procedure, Motivation and Students’ Narrative Reading Comprehension Achievement